2020
DOI: 10.1007/s10803-020-04370-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Suicidality and Its Association with Emotion Regulation Impairment in Large ASD and US Census-Matched Samples

Abstract: Evidence suggests increased rates of suicidality in autism spectrum disorder (ASD), but the research has rarely used comparison samples and the role of emotion dysregulation has not been considered. We compared the prevalence of parent-reported suicidal ideation and considered the role of emotion dysregulation in 330 psychiatric inpatient youth with ASD, 1,167 community youth with ASD surveyed online, and 1,000 youth representative of the US census. The prevalence of suicidal ideation was three and five times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 66 publications
(79 reference statements)
1
26
0
Order By: Relevance
“…Importantly, both Reactivity and Dysphoria were significantly related to the use of psychiatric hospitalization and the emergency services, and Dysphoria has also been associated with increased likelihood of suicidal ideation in a prior ASD study [Conner et al, 2020]. Overall, this emphasizes the importance of screening for both manifestations of ER impairment, as well as a continued need for clinical trials addressing Dysphoria in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both Reactivity and Dysphoria were significantly related to the use of psychiatric hospitalization and the emergency services, and Dysphoria has also been associated with increased likelihood of suicidal ideation in a prior ASD study [Conner et al, 2020]. Overall, this emphasizes the importance of screening for both manifestations of ER impairment, as well as a continued need for clinical trials addressing Dysphoria in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In 481 autistic youth, McDonnell et al (2019) report correlates of suicidal ideation and self-harm/suicide behaviours, notably child age, parental education, restricted and repetitive behaviours, IQ and adaptive behaviour, affective and conduct problems, and medical concerns. Conner et al (2020) showed significantly increased risk of suicidality in autistic youth from the community and psychiatric inpatient samples, and emotion regulation was associated with increased risk of suicidality. Licence et al (2019) showed a 24% parent reported prevalence of self-harm in autistic children and adults.…”
Section: Prevalence and Risk Markersmentioning
confidence: 93%
“…Firstly, ASD incurs severe psychological and financial burdens on families, who must manage multiple issues [3]. Secondly, evidence has suggested that the rates of suicidality increase almost three and five times in ASD community and inpatient samples compared with a control group [4]. Lastly, it is difficult for children with ASD to completely socially integrate, for their symptoms influence communication and socialization throughout the life span [5].…”
Section: Introductionmentioning
confidence: 99%